Poverty and insecurity life in low-pay, no-pay Britain - Shildrick, Tracy 1966-; Macdonald, Robert 1962-; Webster, Colin ca. 20./21. Jh; Garthwaite, Kayleigh ca. 20./21. Jh (Studies in poverty, inequality, and social exclusion, 2012)
This book is the first of its kind to examine the relationship between social exclusion, poverty and the labour market. It challenges long-standing and dominant myths about 'the workless' and 'the poor', by exploring close-up the lived realities of life in low-pay, no-pay Britain